Corrosion assessment of Ti-6Al-4V fabricated using laser powder-bed fusion additive manufacturing. (20th July 2018) - Chiu, Tse-Ming; Mahmoudi, Mohamad; Dai, Wei; Elwany, Alaa; Liang, Hong; Castaneda, Homero
Abstract: We describe the interfacial characteristics of a Ti-6Al-4V alloy fabricated using laser powder-bed fusion (L-PBF) upon exposure to a corrosive environment and tribocorrosion conditions. Electrochemical techniques in both the time and frequency domains demonstrated a correlation between the manufacturing process parameters and corrosion properties, and a titanium oxide passive layer produced specific semiconductor n-type properties. The influence of the microstructure on the titanium oxide passive layer was revealed by comparing L-PBF parts with a traditionally manufactured Ti-6Al-4V alloy in Ringer's simulated body solution. Tribocorrosion characterization reflected the endurance of the surface oxide when the process parameters were adjusted. In addition, wearing simultaneously reflected the mechanical condition as the surface repassivate. The production of fragmentation film during wear caused accumulation of the corrosion product and demonstrated the effect of aggressive ions on the chemical and mechanical properties of the passivation film. Graphical abstract: Image 1 Highlights: Ti-6Al-4V alloys generated by 3D printing were characterized in a tribocorrosion environment. Mechanical property of fragmentation films diminished as chloride increased from 0.6 to 2.8 wt%. A correlation between the microstructures and passivation later properties was suggested.